Two New Legend Variations of a Rare Greek Coin Type from Amyzon - Öhm-Kühnle, Christoph (KOINON: The International Journal of Classical Numismatic Studies, 2023)
Caria’s history is rich. For example, the Greek historian Herodotus was born in Caria’s capital Halicarnassus. Also, the term Mausoleum is named after the Carian satrap Mausolus, whose impressive, elevated tomb (c. 148 ft high) in Halicarnassus was regarded as one of the Seven Wonders of the Ancient World and became the model for this type of architecture. Part of Caria’s history is its coinage, including a rare bronze type with the bust of Herodotus. As with other regions in Asia Minor, many Carian towns had their own coinage, such as Amyzon. Today only ruins remain near the town Gaffarlar in Anatolia/Turkey, near Alinda. Among the Amyzon coinage, which is in general quite rare, there is a type featuring Artemis on the obverse, a kithara on the reverse, and various renditions of the reverse legend. Similar types are known from several other cities, such as the nearby town of Alabanda (featuring laureate Apollo-obverse), as well as another from Halicarnassos (with Helios obverse). The type from Amyzon is overlooked in most standard references. Imhoof-Blumer did describe it in the year 1883, and a variant was soon after described by Anson. In the late 20th century, Robert and Robert described two more variants in their excavation documentation of Amyzon. Since then, however, several new variants have appeared. The purpose of this essay is to present the current state of research on this type and document all specimens and variants known to the author—two of which are newly discovered.